IMPLEMENTASI PERMAINAN TRADISIONAL UNTUK MENGONTROL SOSIAL EMOSIONAL SELAMA PROSES PEMBELAJARAN DARING PADA ANAK USIA SEKOLAH DASAR - Eny Kusumawati; Rika Yuni Ambarsari (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2021)
Emotional social development is one aspect of development for children. Given the importance of children's emotional social development early on The selection of learning activities should be able to stimulate the child to be active, and the child can increase cooperation with peers or adults, so that it can improve social development. One way that can be used as a strategy to overcome children's problems is to create play activities that can develop children's social. Given the importance of children's social emotional development from an early age. Choosing learning activities must be able to stimulate children to be active, and children can increase cooperation with peers or adults, so that it can improve social development. One way that can be used as a strategy to solve children's problems is to create play activities that can develop children's social development. Traditional games are relatively simple but provide amazing benefits. Development that can be improved in traditional games is social emotional in children among others to train cooperation, cohesion, and traction between children with each other. Traditional games used in this activity include engklek, dakon and motion games and songs and other games. In the traditional game offered in this activity many social attitudes contained in it include sportsmanship, cooperation, hard work, respect for others, patience, cohesion, self-control in terms of controlling children's emotions. In addition, children also learn to be responsible, not picky friends, children learn orderly rules and learn to respect others. Thus the stimulation of social skills through traditional games of motion and traditional games can make the child's personal emotional social intelligence. Keywords: social emotional skills, traditional games